2016
DOI: 10.1186/s40463-016-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in CPAP adherence over twenty years of data collection: a flattened curve

Abstract: BackgroundObstructive sleep apnea (OSA) is a common disorder, and continuous airway positive pressure (CPAP) is considered to be the gold standard of therapy. CPAP however is known to have problems with adherence, with many patients eventually abandoning the device. The purpose of this paper is to assess secular trends in CPAP adherence over the long term to see if there have been meaningful improvements in adherence in light of the multiple interventions proposed to do so.MethodsA comprehensive systematic lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
401
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 521 publications
(418 citation statements)
references
References 108 publications
(55 reference statements)
7
401
2
8
Order By: Relevance
“…These studies also based their results on consistent use of CPAP, with higher than average compliance rates, making their findings difficult to reproduce. Although the literature suggests that optimal CPAP use is between 6 to 7 hours per night, long‐term longitudinal data have actually defined CPAP compliance as low as 4.6 hours/night with 30% to 40% noncompliance rates . Our compliance rates were 49.1 hours/week, averaging to a nightly use of about 7 hours.…”
Section: Discussionmentioning
confidence: 76%
“…These studies also based their results on consistent use of CPAP, with higher than average compliance rates, making their findings difficult to reproduce. Although the literature suggests that optimal CPAP use is between 6 to 7 hours per night, long‐term longitudinal data have actually defined CPAP compliance as low as 4.6 hours/night with 30% to 40% noncompliance rates . Our compliance rates were 49.1 hours/week, averaging to a nightly use of about 7 hours.…”
Section: Discussionmentioning
confidence: 76%
“…Acceptance and adherence are important conditions for good CPAP compliance (Rotenberg et al, ). Adherent patients are usually defined as those who use CPAP for an average of 4 hr per night on 70% of nights (Rotenberg et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been demonstrated that early adherence (at one week or one month) is associated with better adherence at six months [20,21]. In a recent literature review, the long-term adherence rate has been estimated at 66% [22]. Factors such as psychological barriers, social concerns, side effects, disease characteristics and first CPAP exposure can affect treatment acceptance and adherence [23] and as many as 5 to 50% of patients refuse treatment or reject it rapidly after initiation [24].…”
Section: Telemonitoring Of Cpap-treated Obstructive Sleep Apnea Symentioning
confidence: 99%